2020
DOI: 10.1371/journal.pone.0238728
|View full text |Cite
|
Sign up to set email alerts
|

Dimensions of aberrant driving behaviors and their association with road traffic injuries among drivers

Abstract: Objective Road traffic injuries (RTIs) are recognized as one of the most important causes of morbidity and mortality throughout the world, especially in developing countries. Human behavior is reportedly one of the critical factors in the occurrence of such injuries. The purpose of this study is to evaluate the correlation of abnormal driving behaviors with the frequency and severity of RTIs among drivers in Hamadan, west of Iran. Methods The present cross-sectional study was conducted on 800 people driving, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…Errors refer to failures of planned actions to achieve intended consequences, whereas violations are deliberate deviations from what is considered safe practice. Both these underlying constructs have been associated with accident involvement in previous studies (de Winter & Dodou, 2010;de Winter et al, 2015;Shams et al, 2020;Rezapur-Shahkolai et al, 2020;Mehdizadeh et al, 2018Mehdizadeh et al, , 2019. However, speeding, inattentive, and fatigued/tired driving seem to be of particular importance in accident causation.…”
Section: Introductionmentioning
confidence: 78%
“…Errors refer to failures of planned actions to achieve intended consequences, whereas violations are deliberate deviations from what is considered safe practice. Both these underlying constructs have been associated with accident involvement in previous studies (de Winter & Dodou, 2010;de Winter et al, 2015;Shams et al, 2020;Rezapur-Shahkolai et al, 2020;Mehdizadeh et al, 2018Mehdizadeh et al, , 2019. However, speeding, inattentive, and fatigued/tired driving seem to be of particular importance in accident causation.…”
Section: Introductionmentioning
confidence: 78%
“…According to data, with increasing age, the risk of an individual suffering from a higher severity of the injury was higher due to insufficient vision and physical abilities to react quickly in emergencies (14). While the results of other studies indicated that with decreasing age, the risk of injury is higher which may arise from ignorance of the rules and insufficient experience (19).…”
Section: Discussionmentioning
confidence: 98%
“…Therefore, it is vital to monitor road safety progress regularly to improve road safety and sustainability within the transportation system [2,3]. Road crashes are complex and multi-faceted events that occur due to the interactions of various factors [4], such as driving behaviour [5][6][7][8][9][10][11], road and vehicle conditions [12], weather conditions [13,14], road geometry and spatial features of the road environment [15] and many others. By developing effective road safety policies and interventions, the likelihood and severity of crashes could be significantly reduced.…”
Section: Introductionmentioning
confidence: 99%